Workplace Democracy and Job Flows - Guillermo Alves; Gabriel Burdín; Andres Dean (Institute for the Study of Labor (IZA), 2014)
This paper investigates the relationship between workplace democracy and job flows (net job creations, gross job creations and destructions) by comparing the behavior of worker-managed firms (WMFs) and conventional firms. The empirical analysis relies on high frequency administrative firm-level panel data from Uruguay over the period April 1996-July 2009. The main findings of the paper are that (1) WMFs exhibit much more stable job dynamics than CFs; (2) both types of firms have decreasing in age and increasing in size gross job creation profiles; (3) there are heterogeneous employment regimes within WMFs: high job creation and destruction rates of hired workers and low job creation and destruction of members. This paper contributes to the literature on the role of institutions in shaping job flows. Our results may have important implications for the understanding of the allocative efficiency effects of worker participation.
Keywords: D21; J54; J63; 330; job flows; worker-managed firms